Gender und Nachhaltigkeit - Sauer, Arn Thorben (My University, 2014)
Der Beitrag gibt einen Einblick in die institutionalisierte Gleichstellungsarbeit im Umweltbundesamt. Er zeigt ihre gesetzlichen Grundlagen und historische Entwicklung auf und beleuchtet ihre Akteur_innen, Aufgaben, Maßnahmen und Instrumente. Der Beitrag kommt zu dem Ergebnis, dass die bestehenden Strategien und Instrumente grundsätzlich zielführend sind, wenn auch Gleichstellung noch nicht überall erreicht ist. Zudem werden eine Diversifizierung von Gleichstellungsthemen und die erhöhte Komplexität in den Anforderungen an die Gleichstellungsakteur_innen attestiert. Insbesondere der Ansatz des GM hat gut zehn Jahre nach seiner Einführung im Rahmen des Nachhaltigkeitsverständnisses des Umweltbundesamtes gerade erst begonnen, sein innovatives Potenzial zu entfalten.

Gender and sustainability – Institutionalised gender equality work and gender mainstreaming at the German Federal Environment Agency This article provides an insight into gender equality work in the German Federal Environment Agency. Legal frameworks and an overview of the historical development of gender equality work at the agency are presented, as well as the actors, issues, tasks and instruments involved. The article attests to the basic efficacy of existing strategies and instruments, despite the fact that gender equality has not yet been achieved in all areas and at all levels of the institution. The article also addresses the increasingly complex, diverse and demanding topics with which actors must contend in the main strands of equality and gender mainstreaming. Ten years after its introduction, gender mainstreaming in particular has only just begun to demonstrate its innovative potential in this context.
institutionalisierte Gleichstellungsarbeit und Gender Mainstreaming im Umweltbundesamt
Keywords: Gender Mainstreaming; 351 Öffentliche Verwaltung; Gleichstellung; Öffentliche Verwaltung; Governance; Instrumente; Akteur_innen; equality; public administration; governance; instruments; actors; gender mainstreaming